Natural parallelisation paradigm on accelerator physics example. (21st October 2019) - Kulabukhova, Nataliia
In this paper the problems of using the existing methods and algorithms for applied science with the help of high performance techniques is described. The idea is to provide the scientists with an easy to use tools for constructing the implementation of their research working on heterogeneous systems. Without a doubt the problem-solving environment for these purposes must give the exact solution in a reasonable time. The concept which is described in the article was devised specifically for such kind of tasks. The application of it in terms of high energy physics is given. To illustrate the work of the concept the analysis of the distribution of the particles in the beam under the influence of the space charge is done.